The effect of dynamic heat treatments of native whey protein concentrate on its dispersion characteristics. (October 2015) - Laiho, Saara; Ercili-Cura, Dilek; Forssell, Pirkko; Myllärinen, Päivi; Partanen, Riitta
Abstract: The aggregation of native whey protein concentrate (WPC) was studied after a range of dynamic heat treatments performed at 0.5%, 3.5%, 5.0% and 8.8% protein concentrations. Overall, it was observed that the changes caused by heating were mainly physical, but higher heat treatments were also found to increase the furosine content, indicating Maillard reactions. Most of the whey proteins remained native after heat treatment at 75 °C for 15 s at all the concentrations studied. Heat treatment at 90 °C for 5 min caused whey proteins to reach the maximum degree of denaturation at 3.5% protein concentration. The size of the aggregates kept growing with increasing protein concentration. At 8.8% protein, essentially all whey protein monomers and low-molecular weight oligomers had reacted, forming insoluble polymers, and only β-casein was left in the solution. Further heat treatments extended shelf life and ultra-high temperature conditions mostly decreased the hydrophobicity.